DETERMINAN FAKTOR KEBIJAKAN DIVIDEN PERUSAHAAN SEKTOR PROPERTI DAN REAL ESTATE DI INDONESIA - Melsanda Farelya Handhany; Maria Safitri; Suhita Whini Setyahuni; Almira Santi Samasta (Politeknik Negeri Ambon, 2025)
Introduction: Indonesia's property and real estate sector is showing a post-pandemic recovery trend, although it is still characterized by a slowdown due to market dynamics and substantial capital requirements. This study analyzes the effect of profitability, liquidity, and leverage on the dividend policy of property companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Methods: The study employed a quantitative approach using secondary data in the form of company financial statements. This research used a sample of 12 property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023, with sample selection based on criteria (purposive sampling). The analytical technique chosen to examine this research was multiple linear regression and t-test utilizing IBM SPSS Statistics software. Results: The research findings show that profitability (ROA), liquidity (CR), and leverage (DER) have a significant negative effect on dividend policy (DPR). From this research, results were obtained showing that companies with high levels of profitability, liquidity, and leverage retain earnings for company operations such as project investments or debt obligation payments rather than distributing them as dividends. Keywords: Profitability, Liquidity, Leverage, Dividend